INTENSIVE CARE NURSING AND INNOVATION IN PATIENT SAFETY PROTOCOLS - Ventureli, Akemyla Bortolucci (Editora Impacto Científico, 2025)
The overall objective of this research is to discuss the role of intensive care nursing in relation to critical patient safety protocols. This is a narrative review, in which the articles were found in the Google Scholar repository. Patient safety in ICUs demands rigorous protocols, continuing education, and strategic action from intensive care nursing. Technological and team failures are avoidable with training and systematization of practices. DOI: https://doi.org/10.56238/edimpacto2025.078-002